Rare Case of Duodenal Metastasis From Pulmonary Squamous Cell Carcinoma - Zain Memon DO; Samson Ferm MD; Constantine Fisher MD; Akil Hassam MD; Jean Luo MD; Sang Hoon Kim MD (SAGE Publishing, 2017)
Pulmonary squamous cell carcinoma is the second most common non-small cell malignancy of the lung. It commonly metastasizes to the adrenal glands, bone, liver, brain, and kidneys. Most occurrences of metastatic squamous cell carcinoma involving the gastrointestinal tract originate from primary lung tumors. Metastasis to the duodenum, however, is exceedingly rare, with very few cases of stomach or duodenal involvement described in the literature. We report the case of a patient with stage IV pulmonary squamous cell carcinoma metastasizing to the duodenum with an uncommon presentation to add to the paucity of literature available regarding this rare finding.